Tactical competition of two airlines in fleet assignment - Yaba, Ceyda. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2015., 2015)
We analyze two airlines competing in the same market at a tactical level using an itinerary-based eet assignment model. The market demand is contingent on the fares chosen by the airlines. The airlines solve their own eet assignment models and can choose to spill customers on some itineraries. The recapture rates of these customers are also contingent on the fares chosen by airlines. Therefore, the dimensions of competition are both the demand and the recapture rates in the same market. Using a logit model for allocating the demand and the recapture rates between the airlines, we seek for equilibrium behavior of the airlines with exogenous fares in a computational setting. We argue that in this tactical level competition, variables like eet type, aircraft capacity is as important as the fares.
Keywords: Airlines -- Planning -- Mathematical models.